Impact of global crisis events on the dependence and risk spillover between gold and crude oil: a regime-switching copula approach - Yuankui Wang; Xiaoquan Ding; Pengwei Wang; Ziwei Huang (Humanities & Social Sciences Communications)
Abstract In recent years, global crisis events have become increasingly common. Gold, recognized as a safe asset, and crude oil, an essential industrial commodity, have attracted the attention of many scholars seeking to understand the impact of such crises on both. On the basis of a Markov regime-switching (MRS) model, copula function, and conditional value at risk (CoVaR) model, this paper proposes an MRS copula CoVaR model to investigate the changes in the level of dependence between these two assets and examine the risk spillover effects between them. This study obtains the following conclusions. (1) From 2018 to 2023, there are two distinct dependence regimes between the two assets. The tranquil regime is characterized by positive dependence, whereas the crisis regime is characterized by negative dependence. (2) In the crisis regime, there is downside risk spillover between the two assets, whereas in the tranquil regime, there is an upside risk spillover. These findings contribute to theoretical research and offer valuable insights for policymakers and investors in making informed decisions and developing appropriate investment strategies.